Axial localization and tracking of self-interference nanoparticles by lateral point spread functions - Yongtao Liu (Nature Portfolio, 2021)
Here, the authors show that single upconversion nanoparticles can generate position-sensitive patterns in the spatial domain when placed on a mirror. They attribute this to the single emitter’s interference with its own mirror image and show how this can be used to obtain axial localisation of the particle.